2019
DOI: 10.1093/mnras/stz2507
|View full text |Cite
|
Sign up to set email alerts
|

Star formation histories of dwarf galaxies in the FIRE simulations: dependence on mass and Local Group environment

Abstract: We study star formation histories (SFHs) of 500 dwarf galaxies (stellar mass M * = 10 5 − 10 9 M ) from FIRE-2 cosmological zoom-in simulations. We compare dwarfs around individual Milky Way (MW)-mass galaxies, dwarfs in Local Group (LG)-like environments, and true field (i.e. isolated) dwarf galaxies. We reproduce observed trends wherein highermass dwarfs quench later (if at all), regardless of environment. We also identify differences between the environments, both in terms of "satellite vs. central" and "LG… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 114 publications
28
70
1
Order By: Relevance
“…Here, we see that there is no significant offset between the AMR of the satellites and centrals. This result is in agreement with findings by Garrison-Kimmel et al (2019), who studied the SFHs of dwarf galaxies with a range of masses in the Feedback In Realistic Environments (FIRE)-2 simulations (Hopkins et al 2018). Specifically, these authors compared the SFHs of satellite galaxies and centrals, and found that for L/SMC-mass galaxies (see Section 4), the SFH of centrals near MW-mass galaxies were most alike the SFH of the LMC and SMC galaxies.…”
Section: E N T R a L S V E R S U S S At E L L I T E Ssupporting
confidence: 92%
“…Here, we see that there is no significant offset between the AMR of the satellites and centrals. This result is in agreement with findings by Garrison-Kimmel et al (2019), who studied the SFHs of dwarf galaxies with a range of masses in the Feedback In Realistic Environments (FIRE)-2 simulations (Hopkins et al 2018). Specifically, these authors compared the SFHs of satellite galaxies and centrals, and found that for L/SMC-mass galaxies (see Section 4), the SFH of centrals near MW-mass galaxies were most alike the SFH of the LMC and SMC galaxies.…”
Section: E N T R a L S V E R S U S S At E L L I T E Ssupporting
confidence: 92%
“…The τ 90 of these galaxies were found from 7.4 to 5.2 Gyr ago ( ( ) = t log yr 9.87-9.72) by Weisz et al (2015), and the quenching time of And VII, with the largest mass, is later than most if not all of them. Our results confirm the observed relation that lower-mass dwarfs typically cease stellar mass assembly earlier than higher-mass galaxies (Weisz et al 2015;Garrison-Kimmel et al 2019). We note that these five galaxies are located within the M31 virial radius, where the quenching time is thus essentially independent of the current proximity to M31 (Weisz et al 2015).…”
Section: Cumulative Sfh and Quenching Timesupporting
confidence: 89%
“…White & Frenk 1991), assume that a significant gas fraction has already cooled and settled well inside the virial radius. In accordance with observations (Behroozi et al 2013) and simulations of galaxy formation (Garrison-Kimmel et al 2019), we also assume that at this stage only a fraction < ∼ 0.2 of the final stellar mass has formed 2 . As the (gas rich) satellite orbits into the parent halo, it begins to lose matter from its outer parts by the tidal gravitational forces of the parent halo.…”
Section: The Set-upsupporting
confidence: 78%